2004
DOI: 10.1089/105072504322783812
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Clinical and Ultrasonographic Characteristics of Thyroid Incidentalomas

Abstract: High-resolution ultrasonography (US) has made possible the detection of asymptomatic small thyroid nodules. Thyroid incidentalomas have created a clinical dilemma as to how to properly manage such incidental findings. We investigated the prevalence, the clinical and US characteristics, and optimal diagnostic approach to incidentally detected benign and malignant thyroid nodules < 1.5 cm. Retrospective review was done on 1475 patients who had visited Samsung Medical Center, Soul Korea from January 1999 to Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
114
4
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(138 citation statements)
references
References 12 publications
16
114
4
4
Order By: Relevance
“…For examples, Frates et al perfomed USgFNAC selectively on patients with nodule larger than 1 cm [9]. In other studies, only thyroid nodules less than 1.5 cm were aspirated by sonographic guidance for cytologic examination [4,8]. However, it has been routine practice at our clinic to refer all patients with incidental thyroid nodules to radiologists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For examples, Frates et al perfomed USgFNAC selectively on patients with nodule larger than 1 cm [9]. In other studies, only thyroid nodules less than 1.5 cm were aspirated by sonographic guidance for cytologic examination [4,8]. However, it has been routine practice at our clinic to refer all patients with incidental thyroid nodules to radiologists.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have examined the relationship between sonographic features of thyroid nodules and malignancy [4,8,9]. Recent recommendations suggest FNAC for most nodules greater than 10-15 mm, particularly those with suspected malignancy based on sonographic features and in cases of multiple nodules, FNAC should be based on the sonographic features rather than size of each nodule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the number of thyroid cancer cases detected in Korea has increased dramatically because of the widespread use of high-resolution ultrasonography and fine-needle aspiration cytology [2,3]. Because most patients with differentiated thyroid cancer require HDRIT after surgery, a shortage of available isolation rooms has resulted.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the incidence of such thyroid incidentalomas to be between 19% and 46% for ultrasonography and about 16% for CT and MRI. 8,14 The risk of malignancy in these lesions is relatively low, ranging from 1.5% to 10.0%. 15 With the increasing use of FDG-PET in the evaluation and surveillance of patients with cancer, a substantial number of patients will present with incidentally identified focal uptake within the thyroid, 1 which we refer to as a "PEToma."…”
Section: Discussionmentioning
confidence: 99%